Hubungan antara Strategi Koping dengan Distres Psikologi pada Perawat di Masa Pandemi COVID-19 - Qanita, Zalfa; Cahyanti, Ika Yuniar (Buletin Riset Psikologi dan Kesehatan Mental, 2023)
The COVID-19 pandemic has significantly impacted the healthcare sector, particularly among healthcare professionals, such as nurses. Many nurses have experienced psychological distress during the pandemic. Psychological distress itself is closely related to how a person makes coping efforts. Therefore, this study aimed to see the relationship between coping strategies (problem-focused, emotion-focused, and dysfunctional coping) and psychological distress in nurses during the COVID-19 pandemic. The participants in this quantitative study were 48 nurses who are currently or have previously worked in handling COVID-19 cases. The measurement tools utilized were the Brief-COPE for assessing coping strategies and the General Health Questionnaire-12 for measuring psychological distress The results of correlation test analysis revealed that there is no significant relationship between coping strategies and psychological distress in nurses during the COVID-19 pandemic.